2018
DOI: 10.1002/ajp.22749
|View full text |Cite
|
Sign up to set email alerts
|

Captive chimpanzee (Pan troglodytes) behavior as a function of space per animal and enclosure type

Abstract: Space per animal, or animal density, and enclosure type are important elements of functionally appropriate captive environments (FACEs) for chimpanzees. The National Institutes of Health (NIH) recommends that captive chimpanzees be maintained in areas of >250 ft /animal. Several studies have investigated chimpanzee behavior in relation to space per animal, but only two studies have examined these variables while attempting to hold environmental complexity constant. Both have found few, if any, significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…While three studies have found a significant inverse relationship (Asiatic lion [ 22 ], New Zealand white rabbits [ 23 ], bottlenose dolphins [ 24 ]), a study on two bear species found no significant relationship [ 25 ]. Studies examining both behavioral diversity and stereotypic behavior but not comparing them statistically have generally found that when stereotypic behavior is high or increased, behavioral diversity is low or decreased (sows [ 21 ], small felids [ 26 ], large felids [ 27 ], giant pandas [ 28 , 29 ], spectacled bears [ 30 ], chimpanzees [ 31 ], African elephants [ 32 ], parakeets [ 33 ], and songbirds [ 34 ]). Similarly, pharmacologically induced stereotypic behavior was also associated with lower behavioral diversity [ 35 ].…”
Section: Behavioral Diversity and Stereotypic Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…While three studies have found a significant inverse relationship (Asiatic lion [ 22 ], New Zealand white rabbits [ 23 ], bottlenose dolphins [ 24 ]), a study on two bear species found no significant relationship [ 25 ]. Studies examining both behavioral diversity and stereotypic behavior but not comparing them statistically have generally found that when stereotypic behavior is high or increased, behavioral diversity is low or decreased (sows [ 21 ], small felids [ 26 ], large felids [ 27 ], giant pandas [ 28 , 29 ], spectacled bears [ 30 ], chimpanzees [ 31 ], African elephants [ 32 ], parakeets [ 33 ], and songbirds [ 34 ]). Similarly, pharmacologically induced stereotypic behavior was also associated with lower behavioral diversity [ 35 ].…”
Section: Behavioral Diversity and Stereotypic Behaviormentioning
confidence: 99%
“…In total, across 28 studies, there was a reported increase in behavioral diversity (decrease for lack of enrichment) for 78.6% of the studies, with the remaining 21.4% reporting no significant difference. Species that experienced an increase in behavioral diversity following enrichment or an enhanced habitat included big cats [ 27 , 45 , 46 ], leopard geckos [ 38 ], parakeets [ 33 ], capuchins [ 40 ], African cichlid males [ 47 ], pigs [ 21 , 48 , 49 , 50 ], wombats [ 39 ], red foxes [ 51 ], bottlenose dolphins [ 52 ], ghost bats [ 53 ], bears (spectacled [ 30 ], Andean, sloth, brown, and black [ 54 ]), rats [ 55 ], African elephants [ 32 ], small felids [ 26 ], hognose snakes [ 56 ], giant pandas [ 28 , 29 ], and chimpanzees [ 31 ]. Species where enrichment or improved habitat was not found to significantly change behavioral diversity include armadillos, bush babies, and two toed sloths [ 57 ], wolves [ 58 ], African elephants [ 59 ], zebra fish and checker barbs [ 60 ], and lions [ 41 ].…”
Section: Factors Affecting Behavioral Diversitymentioning
confidence: 99%
“…Reamer et al (2016) found that chimpanzees housed in groups of seven or more exhibited higher levels of affiliative and abnormal behavior compared to groups of six or fewer. As part of a larger project that examines the behavioral effects of captive environments and refinements to behavioral management techniques (Neal Webb, Hau, & Schapiro, 2018a, 2018b), the current study aimed to empirically examine group size and group composition recommendations to provide additional data for use in defining captive chimpanzee FACEs. Specifically, we explored whether the behavior of captive chimpanzees housed in groups ranging from 4 to 10 animals differed as a function of 1) group size; 2) the percentage of males within the group; 3) within-group age range; and 4) interactions between these variables.…”
Section: Introductionmentioning
confidence: 99%
“…They spent less time resting during the control period as well, which may be related to the typically active behavior of capuchins (Ross, 1988;Zhang, 1995). Even if the enclosure size may affect locomotion rates (Webb et al,2018), we believe that this result is mostly related to the fact that wild capuchins have high foraging and traveling rates, as well as low rates of resting and social interactions (Rímoli et al, 2008). Even in captivity capuchins can spend much of their energy in vertical (~45 m/hr) and horizontal (541 m/hr) travel throughout the day (Edwards et al, 2017).…”
Section: Discussionmentioning
confidence: 90%